Adhesive glass slide and preparation method thereof

By hydroxylation of the slide and activation of silane coupling agent, and coating with adhesion solution of polyethyleneimine, chitosan and other materials, the problems of low adhesion effect and poor stability are solved, and efficient and uniform cell or tissue adsorption is achieved, with clean background color, suitable for industrial applications.

CN119804056APending Publication Date: 2025-04-11SHAOXING RES INST OF ZHEJIANG UNIV
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411855413.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The adhesion effect of existing adhesive slides is not high, has poor stability, and has the problem of background color interference.

Method used

By hydroxylation treatment on the slide and activation treatment of silane coupling agent, the surface is coated with an adhesion solution composed of polyethyleneimine, chitosan, surfactant and additives to form a high-density positive charge surface to improve adhesion uniformity and stability.

Benefits of technology

It achieves excellent adhesion performance and uniformity of the slide, can stably adsorb cells or tissues, has a clean background color, and is simple in preparation and low in cost, which is suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119804056A_ABST
    Figure CN119804056A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biological auxiliary materials, and discloses an adhesive glass slide and a preparation method thereof.The preparation method comprises the steps that a hydroxylated glass slide is placed in a silane coupling agent solution to be activated, and the activated glass slide is obtained after cleaning and drying; and coating the surface with an adhesive solution, and drying to obtain the adhesive glass slide, the adhesion solution is prepared from the following components in percentage by mass in the solution: 1 to 3 percent of polyethyleneimine, 0.2 to 1 percent of chitosan, 0.05 to 0.1 percent of a surfactant and 0.02 to 0.2 percent of an auxiliary agent. According to the invention, the activated glass slide is coated with the adhesion solution mainly comprising polyethyleneimine and chitosan, so that high-density positive charges can be obtained on the surface of the glass slide, the glass slide can be uniformly and favorably adhered to tissues or cells, the adhesion is stable and not easy to fall off, the preparation is simple and convenient, the storage is stable, and the problem of background color interference hardly exists.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biological auxiliary materials, and in particular to an adhesive glass slide and a preparation method thereof. Background Art

[0002] Adhesive slides are surface treated slides, commonly used in liquid-based cytology thin layer preparation, pathology preparation, cell culture, etc., to prevent cells or tissues from falling off the slide during operation. An ideal adhesive slide should be able to achieve rapid adhesion to cells to improve detection efficiency, and be able to ensure the amount of cell adhesion to avoid false negative test results. The adhesion principle of adhesive slides in the prior art can be divided into the principle of attraction between positive and negative charges, adhesive adhesion, etc. Since most cells are negatively charged as a whole, when encountering a positively charged functional coating, they will selectively adsorb on the surface of the functional coating, such as polylysine, aminosilane, etc., on the surface of most adhesive slides.

[0003] There are various methods for making adhesive glass slides, such as polylysine soaking method, APES silanization method, collagen smear method, etc. CN104502619A discloses a method for preparing a hydrophilic adhesive glass slide and a method for using the same. The glass slide is pretreated with an aminosilane solution with a volume concentration of 0.8-8% or a polylysine solution with a volume concentration of 0.1-1%, washed with water, dried, and then soaked in an albumin solution with a mass concentration of 0.5-5%, then taken out, washed with water, and dried to obtain a hydrophilic adhesive glass slide. The surface of the hydrophilic glass slide has hydrophilic groups, good compatibility with biological macromolecules, strong adhesion performance, and makes it easy for aqueous reagents to spread evenly on the surface of the glass slide, overcoming the disadvantage that ordinary adhesive glass slides often have uneven staining when used on automatic immunohistochemistry instruments.

[0004] CN112945671A discloses an adhesive glass slide and its preparation method and application. By a simple soaking and drying method, a polymer adhesive coating such as polyethylene glycol, polyvinyl pyrrolidone, polyethyleneimine, etc. is coated on the surface of the glass slide substrate to obtain a glass slide with cell adhesion ability. The glass slide has good adhesion effect and will not damage the adhered cells. The morphological characteristics of the cells can be well observed, which solves the problem of expensive raw materials and unstable adhesion effect of existing adhesive glass slides. It is convenient for clinical thin-layer cytology detection and analysis of different diseased cells, effectively avoids the occurrence of false negative results, and has broad market prospects.

[0005] However, these methods still have problems such as high preparation cost, poor adhesion effect, poor stability, and background color interference. Summary of the invention

[0006] The invention aims to solve the problems that the adhesion effect of the adhesion glass slide is not high and the stability is poor, and provides a method for preparing the adhesion glass slide. The glass slide obtained by the method has excellent adhesion performance and uniform adhesion, can stably and uniformly adsorb cells or tissues, and has a clean background color.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing an adhesive slide comprises the steps of:

[0009] Step 1, hydroxylating the glass slide;

[0010] Step 2, placing the glass slide treated in step 1 in a silane coupling agent solution for activation treatment, washing and drying to obtain an activated glass slide;

[0011] Step 3, coating the surface of the activated glass slide in step 2 with an adhesive solution, and drying to obtain the adhesive glass slide;

[0012] According to the mass fraction in the solution, the adhesion solution includes 1-3% polyethyleneimine, 0.2-1% chitosan, 0.05-0.1% surfactant and 0.02-0.2% auxiliary agent.

[0013] In the present invention, after the glass slide is hydroxylated, the surface is treated with a silane coupling agent to have a positive charge, and polyethyleneimine and chitosan are added to synergistically increase the positive charge density on the surface; adding a surfactant to the adhesion solution is conducive to the uniform spread of the adhesion coating solution on the surface of the glass slide, making the adhesion coating more uniform. The obtained glass slide has excellent adhesion performance and uniform adhesion, can stably and uniformly adsorb cells or tissues, and has a clean background color. The preparation method is simple, fast, efficient, and low in cost, which is conducive to industrial promotion and application.

[0014] The surfactant is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium octyl sulfonate, and potassium octyl sulfonate;

[0015] The auxiliary agent is polyethylene glycol and sodium citrate, wherein the mass fraction of polyethylene glycol is 0.05-0.2%, and the mass fraction of sodium citrate is 0.025-0.1%. The sodium citrate added to the adhesion solution can cross-link with chitosan to enhance the strength of the adhesion coating; the added polyethylene glycol can reduce the adsorption of the coating to the dye, making it easier to observe the tissue or cells under a microscope after the adhesion slide is adsorbed. Preferably, the mass ratio of polyethylene glycol to sodium citrate is 2:0.8-1.2.

[0016] The weight average molecular weight of the polyethyleneimine is 100,000-750,000. The molecular weight of polyethyleneimine affects the adhesion effect to a certain extent. The higher the molecular weight, the more positive charges on the surface of the slide after treatment, and the better the adhesion effect. Preferably, the weight average molecular weight of the polyethyleneimine is 500,000-750,000.

[0017] The silane coupling agent includes one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, 3-diamino-methyl-cyclohexyltriethoxysilane, and γ-aminoethylaminopropyltrimethoxysilane;

[0018] The volume fraction of the silane coupling agent in the silane coupling agent solution is 0.2-1%, and the ethanol aqueous solution with a volume fraction of 93-96% is used as the solvent.

[0019] In step 1, the hydroxylation treatment is to place the glass slide in a 0.8-1 mol / L sodium hydroxide solution and treat it at 60-80° C. for 15-30 minutes.

[0020] In step 2, the activation treatment temperature is 50-60°C and the treatment time is 1-3h.

[0021] The drying is carried out at 60-80°C for 10-60 minutes.

[0022] The invention also provides an adhesive slide prepared according to the preparation method.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The invention uses polyethyleneimine and chitosan as the main adhesion solution to coat the activated glass slide, which can obtain high-density positive charges on the surface of the glass slide, adhere tissues or cells evenly and favorably, adhere stably and not easy to fall off, is easy to prepare, stable in storage, and has almost no background color interference problem. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a comparison chart of the Congo red test results of the glass slides of the embodiment and the comparative example.

[0026] Figure 2 It is a comparison chart of the slide cell adhesion test results of the embodiment and the comparative example. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0028] The γ-aminopropyltriethoxysilane, chitosan, polyethyleneimine, sodium lauryl sulfate, polyethylene glycol and sodium citrate used in the following specific embodiments were purchased from Aladdin Biochemical Technology Co., Ltd., polyethyleneimine was purchased from Yuanye Biotechnology Co., Ltd., and other raw materials not specifically mentioned were purchased from the market.

[0029] Example 1

[0030] Step 1, hydroxylation treatment: place an untreated ordinary glass slide in a 1M sodium hydroxide solution, immerse the working area of ​​the glass slide completely in the solution, heat it at 70°C for 20 minutes, rinse it with ultrapure water, and dry it for later use;

[0031] Step 2, activation treatment: the volume fraction of silane coupling agent is 0.25%, the volume fraction of anhydrous ethanol is 95%, and the rest is supplemented by ultrapure water and stirred evenly for use; immerse the glass slide prepared in step 1 in the silane solution, heat it at 60°C for 1.5h, wash it with anhydrous ethanol, and put it in an oven to dry for use;

[0032] Step 3, prepare an adhesive coating solution: 2% polyethyleneimine with a weight average molecular weight of 100,000, 0.5% chitosan, 0.1% sodium dodecyl sulfate, 0.1% polyethylene glycol, 0.05% sodium citrate, and the rest is supplemented by ultrapure water, dissolved and set aside;

[0033] Step 4, adhesion coating treatment: Use a brush to dip the adhesion coating solution prepared in step 3, brush it on the working area of ​​the slide treated in step 3, place it in an oven and heat it at 60°C for 30 minutes to dry it, then take it out, and the preparation of the adhesion slide is completed.

[0034] Example 2

[0035] Step 1, hydroxylation treatment: place an untreated ordinary glass slide in a 1M sodium hydroxide solution, immerse the working area of ​​the glass slide completely in the solution, heat it at 70°C for 20 minutes, rinse it with ultrapure water, and dry it for later use;

[0036] Step 2, activation treatment: the volume fraction of silane coupling agent is 0.25%, the volume fraction of anhydrous ethanol is 95%, and the rest is supplemented by ultrapure water and stirred evenly for use; immerse the glass slide prepared in step 1 in the silane solution, heat it at 60°C for 1.5h, wash it with anhydrous ethanol, and put it in an oven to dry for use;

[0037] Step 3, prepare an adhesive coating solution: 2% polyethyleneimine with a weight average molecular weight of 300,000, 0.5% chitosan, 0.1% sodium dodecyl sulfate, 0.1% polyethylene glycol, 0.05% sodium citrate, and the rest is supplemented by ultrapure water, dissolved and set aside;

[0038] Step 4, adhesion coating treatment: Use a brush to dip the adhesion coating solution prepared in step 3, brush it on the working area of ​​the slide treated in step 3, place it in an oven and heat it at 60°C for 30 minutes to dry it, then take it out, and the preparation of the adhesion slide is completed.

[0039] Example 3

[0040] Step 1, hydroxylation treatment: place an untreated ordinary glass slide in a 1M sodium hydroxide solution, immerse the working area of ​​the glass slide completely in the solution, heat it at 70°C for 20 minutes, rinse it with ultrapure water, and dry it for later use;

[0041] Step 2, activation treatment: the volume fraction of silane coupling agent is 0.25%, the volume fraction of anhydrous ethanol is 95%, and the rest is supplemented by ultrapure water and stirred evenly for use; immerse the glass slide prepared in step 1 in the silane solution, heat it at 60°C for 1.5h, wash it with anhydrous ethanol, and put it in an oven to dry for use;

[0042] Step 3, prepare an adhesive coating solution: 2% polyethyleneimine with a weight average molecular weight of 500,000, 0.5% chitosan, 0.1% sodium dodecyl sulfate, 0.1% polyethylene glycol, 0.05% sodium citrate, and the rest is supplemented by ultrapure water, dissolved and set aside;

[0043] Step 4, adhesion coating treatment: Use a brush to dip the adhesion coating solution prepared in step 3, brush it on the working area of ​​the slide treated in step 3, place it in an oven and heat it at 60°C for 30 minutes to dry it, then take it out, and the preparation of the adhesion slide is completed.

[0044] Example 4

[0045] Step 1, hydroxylation treatment: place an untreated ordinary glass slide in a 1M sodium hydroxide solution, immerse the working area of ​​the glass slide completely in the solution, heat it at 70°C for 20 minutes, rinse it with ultrapure water, and dry it for later use;

[0046] Step 2, activation treatment: the volume fraction of silane coupling agent is 0.25%, the volume fraction of anhydrous ethanol is 95%, and the rest is supplemented by ultrapure water and stirred evenly for use; immerse the glass slide prepared in step 1 in the silane solution, heat it at 60°C for 1.5h, wash it with anhydrous ethanol, and put it in an oven to dry for use;

[0047] Step 3, prepare an adhesive coating solution: 2% polyethyleneimine with a weight average molecular weight of 750,000, 0.5% chitosan, 0.1% sodium dodecyl sulfate, 0.1% polyethylene glycol, 0.05% sodium citrate, and the rest is supplemented by ultrapure water, dissolved and set aside;

[0048] Step 4, adhesion coating treatment: Use a brush to dip the adhesion coating solution prepared in step 3, brush it on the working area of ​​the slide treated in step 3, place it in an oven and heat it at 60°C for 30 minutes to dry it, then take it out, and the preparation of the adhesion slide is completed.

[0049] Example 5

[0050] Step 1, hydroxylation treatment: place an untreated ordinary glass slide in a 1M sodium hydroxide solution, immerse the working area of ​​the glass slide completely in the solution, heat it at 70°C for 20 minutes, rinse it with ultrapure water, and dry it for later use;

[0051] Step 2, activation treatment: the volume fraction of silane coupling agent is 0.25%, the volume fraction of anhydrous ethanol is 95%, and the rest is supplemented by ultrapure water and stirred evenly for use; immerse the glass slide prepared in step 1 in the silane solution, heat it at 60°C for 1.5h, wash it with anhydrous ethanol, and put it in an oven to dry for use;

[0052] Step 3, prepare an adhesive coating solution: 2% polyethyleneimine with a weight average molecular weight of 500,000, 0.25% chitosan, 0.1% sodium dodecyl sulfate, 0.1% polyethylene glycol, 0.05% sodium citrate, and the rest is supplemented by ultrapure water, dissolved and set aside;

[0053] Step 4, adhesion coating treatment: Use a brush to dip the adhesion coating solution prepared in step 3, brush it on the working area of ​​the slide treated in step 3, place it in an oven at 60°C for 30 minutes, dry it, and then take it out to complete the preparation of the adhesion slide.

[0054] Example 6

[0055] Step 1, hydroxylation treatment: place an untreated ordinary glass slide in a 1M sodium hydroxide solution, immerse the working area of ​​the glass slide completely in the solution, heat it at 70°C for 20 minutes, rinse it with ultrapure water, and dry it for later use;

[0056] Step 2, activation treatment: the volume fraction of silane coupling agent is 0.25%, the volume fraction of anhydrous ethanol is 95%, and the rest is supplemented by ultrapure water and stirred evenly for use; immerse the glass slide prepared in step 1 in the silane solution, heat it at 60°C for 1.5h, wash it with anhydrous ethanol, and put it in an oven to dry for use;

[0057] Step 3, prepare an adhesive coating solution: 2% polyethyleneimine with a weight average molecular weight of 500,000, 0.5% chitosan, 0.1% sodium dodecyl sulfate, 0.05% polyethylene glycol, 0.025% sodium citrate, and the rest is supplemented by ultrapure water, dissolved and set aside;

[0058] Step 4, adhesion coating treatment: Use a brush to dip the adhesion coating solution prepared in step 3, brush it on the working area of ​​the slide treated in step 3, place it in an oven at 60°C for 30 minutes, dry it, and then take it out to complete the preparation of the adhesion slide.

[0059] Comparative Example 1 No surfactant

[0060] Step 1, hydroxylation treatment: place an untreated ordinary glass slide in a 1M sodium hydroxide solution, immerse the working area of ​​the glass slide completely in the solution, heat it at 70°C for 20 minutes, rinse it with ultrapure water, and dry it for later use;

[0061] Step 2, activation treatment: the volume fraction of silane coupling agent is 0.25%, the volume fraction of anhydrous ethanol is 95%, and the rest is supplemented by ultrapure water and stirred evenly for use; immerse the glass slide prepared in step 1 in the silane solution, heat it at 60°C for 1.5h, wash it with anhydrous ethanol, and put it in an oven to dry for use;

[0062] Step 3, prepare an adhesive coating solution: 2% polyethyleneimine with a weight average molecular weight of 500,000, 0.5% chitosan, 0.1% polyethylene glycol, 0.05% sodium citrate, and the rest is supplemented by ultrapure water, dissolved and set aside;

[0063] Step 4, adhesion coating treatment: Use a brush to dip the adhesion coating solution prepared in step 3, brush it on the working area of ​​the slide treated in step 3, place it in an oven at 60°C for 30 minutes, dry it, and then take it out to complete the preparation of the adhesion slide.

[0064] Comparative Example 2 without polyethylene glycol

[0065] Step 1, hydroxylation treatment: place an untreated ordinary glass slide in a 1M sodium hydroxide solution, immerse the working area of ​​the glass slide completely in the solution, heat it at 70°C for 20 minutes, rinse it with ultrapure water, and dry it for later use;

[0066] Step 2, activation treatment: the volume fraction of silane coupling agent is 0.25%, the volume fraction of anhydrous ethanol is 95%, and the rest is supplemented by ultrapure water and stirred evenly for use; immerse the glass slide prepared in step 1 in the silane solution, heat it at 60°C for 1.5h, wash it with anhydrous ethanol, and put it in an oven to dry for use;

[0067] Step 3, prepare an adhesive coating solution: 2% polyethyleneimine with a weight average molecular weight of 500,000, 0.5% chitosan, 0.1% sodium dodecyl sulfate, 0.05% sodium citrate, and the rest is supplemented by ultrapure water, dissolved and set aside;

[0068] Step 4, adhesion coating treatment: Use a brush to dip the adhesion coating solution prepared in step 3, brush it on the working area of ​​the slide treated in step 3, place it in an oven at 60°C for 30 minutes, dry it, and then take it out to complete the preparation of the adhesion slide.

[0069] Comparative Example 3 without sodium citrate

[0070] Step 1, hydroxylation treatment: place an untreated ordinary glass slide in a 1M sodium hydroxide solution, immerse the working area of ​​the glass slide completely in the solution, heat it at 70°C for 20 minutes, rinse it with ultrapure water, and dry it for later use;

[0071] Step 2, prepare silane solution: the volume fraction of silane coupling agent is 0.25%, the volume fraction of anhydrous ethanol is 95%, and the rest is supplemented by ultrapure water and stirred evenly for use;

[0072] Step 3: silanization treatment: immerse the glass slide prepared in step 1 in a silane solution, heat it at 60°C for 1.5h, wash it with anhydrous ethanol, and dry it in an oven for later use;

[0073] Step 4, prepare an adhesive coating solution: 2% polyethyleneimine with a weight average molecular weight of 500,000, 0.5% chitosan, 0.1% sodium dodecyl sulfate, 0.1% polyethylene glycol, and the rest is supplemented by ultrapure water, dissolved and set aside;

[0074] Step 5: Adhesion coating treatment: Use a brush to dip the adhesion coating solution prepared in step 4, brush it on the working area of ​​the slide treated in step 3, place it in an oven at 60°C for 30 minutes, dry it, and then take it out to complete the preparation of the adhesion slide.

[0075] Comparative Example 4 without chitosan

[0076] Step 1, hydroxylation treatment: place an untreated ordinary glass slide in a 1M sodium hydroxide solution, immerse the working area of ​​the glass slide completely in the solution, heat it at 70°C for 20 minutes, rinse it with ultrapure water, and dry it for later use;

[0077] Step 2, activation treatment: the volume fraction of silane coupling agent is 0.25%, the volume fraction of anhydrous ethanol is 95%, and the rest is supplemented by ultrapure water and stirred evenly for use; immerse the glass slide prepared in step 1 in the silane solution, heat it at 60°C for 1.5h, wash it with anhydrous ethanol, and put it in an oven to dry for use;

[0078] Step 3, prepare an adhesion coating solution: 2% polyethyleneimine with a weight average molecular weight of 500,000, 0.1% sodium dodecyl sulfate, 0.1% polyethylene glycol, 0.05% sodium citrate, and the rest is supplemented by ultrapure water, dissolved and set aside;

[0079] Step 4, adhesion coating treatment: Use a brush to dip the adhesion coating solution prepared in step 3, brush it on the working area of ​​the slide treated in step 3, place it in an oven at 60°C for 30 minutes, dry it, and then take it out to complete the preparation of the adhesion slide.

[0080] Comparative Example 5: No Polyethyleneimine

[0081] Step 1, hydroxylation treatment: place an untreated ordinary glass slide in a 1M sodium hydroxide solution, immerse the working area of ​​the glass slide completely in the solution, heat it at 70°C for 20 minutes, rinse it with ultrapure water, and dry it for later use;

[0082] Step 2, activation treatment: the volume fraction of silane coupling agent is 0.25%, the volume fraction of anhydrous ethanol is 95%, and the rest is supplemented by ultrapure water and stirred evenly for use; immerse the glass slide prepared in step 1 in the silane solution, heat it at 60°C for 1.5h, wash it with anhydrous ethanol, and put it in an oven to dry for use;

[0083] Step 3, prepare an adhesive coating solution: chitosan 0.25%, sodium dodecyl sulfate 0.1%, polyethylene glycol 0.1%, sodium citrate 0.05%, and the rest is supplemented by ultrapure water, dissolved and set aside;

[0084] Step 4, adhesion coating treatment: Use a brush to dip the adhesion coating solution prepared in step 3, brush it on the working area of ​​the slide treated in step 3, place it in an oven at 60°C for 30 minutes, dry it, and then take it out to complete the preparation of the adhesion slide.

[0085] Finished product performance analysis

[0086] 350 slides were processed according to the methods of the embodiments of the present invention and the comparative examples, at least 10 slides were processed for each embodiment, and the overall situation was observed.

[0087] (1) Congo red staining

[0088] Under the same conditions, the untreated ordinary glass slide and the adhesive glass slide obtained in the embodiment and the comparative example were stained with Congo red dye for 10 minutes, washed with running water, and the surface adsorption of Congo red dye was observed to determine the surface positive charge density. The results are as follows: Figure 1 shown.

[0089] Depend on Figure 1 It can be seen that the positive charge density on the surface of the adhesive slides prepared in Examples 2, 3, and 4 is larger and more uniform. In Example 1, polyethyleneimine with a lower molecular weight is used, and the positive charge density on the surface is reduced; in Example 5, the chitosan concentration in the adhesive solution is reduced, and the positive charge density on the surface is reduced; in Example 6, the concentrations of polyethylene glycol and sodium citrate in the adhesive solution are reduced, and the positive charge density on the surface is slightly reduced.

[0090] Compared with Example 3, Comparative Example 1 does not add the surfactant sodium dodecyl sulfate, and the uniformity of the surface coating is reduced; Compared with Example 3, Comparative Example 2 does not add polyethylene glycol, and the coating is also relatively uniform, but the surface positive charge density is slightly lower; Compared with Example 3, Comparative Example 3 does not add sodium citrate, the strength of the coating is weak, and the coating is uneven after cleaning; Compared with Example 3, Comparative Example 4 does not add chitosan, and the positive charge on the coating surface is greatly reduced; Compared with Example 3, Comparative Example 5 does not add polyethyleneimine, and the positive charge density on the coating surface is greatly reduced.

[0091] (2) Cell adhesion assay

[0092] Under the same conditions, the untreated ordinary glass slides and the adhesion slides obtained in the examples and comparative examples were subjected to the cervical exfoliated cell adhesion test, and the cell adhesion effect was observed under a microscope after staining. The adhesion results are shown in FIG. Figure 2 As shown, 20 slices were taken for cell adhesion experiment, and the average value was taken as the statistical result and recorded in Table 1.

[0093] Table 1 Statistical results of cell adhesion experiment

[0094]

[0095] Combination Figure 2 As shown in the results of Table 1, the adhesion slides prepared in Examples 3 and 4 have the best effect, with no obvious staining interference and the best adhesion effect. In Examples 1 and 2, polyethyleneimine with a lower molecular weight was used, and the number of cell adhesions was also reduced to a certain extent, but the overall uniformity was good; in Example 5, the chitosan concentration in the adhesion solution was reduced, and the number of cell adhesions was also reduced to a certain extent; in Example 6, the concentrations of polyethylene glycol and sodium citrate were reduced, and the number of cell adhesions was also reduced to a certain extent.

[0096] Compared with Example 3, Comparative Example 1 does not add the surfactant sodium dodecyl sulfate, the uniformity of the surface coating is reduced, and the number of cell adhesion is also reduced to a certain extent; Compared with Example 3, Comparative Example 2 does not add PEG, the coating is also more uniform, but has greater staining interference, the background color of the cell-free area is more obvious, and the number of cell adhesion is also reduced to a certain extent; Compared with Example 3, Comparative Example 3 does not add sodium citrate, the strength of the coating is weak, and the coating is unstable after cleaning, so the number of cell adhesion is also reduced to a certain extent; Compared with Example 3, Comparative Example 4 does not add chitosan, and the number of cells is significantly reduced; Compared with Example 3, Comparative Example 5 does not add polyethyleneimine, and the number of cell adhesion is significantly reduced.

Claims

1. A method for preparing an adhesive slide, characterized in that: Includes steps: Step 1, hydroxylating the glass slide; Step 2, placing the glass slide treated in step 1 in a silane coupling agent solution for activation treatment, washing and drying to obtain an activated glass slide; Step 3, coating the surface of the activated glass slide in step 2 with an adhesive solution, and drying to obtain the adhesive glass slide; According to the mass fraction in the solution, the adhesion solution includes 1-3% polyethyleneimine, 0.2-1% chitosan, 0.05-0.1% surfactant and 0.02-0.2% auxiliary agent.

2. The method for preparing an adhesive slide according to claim 1, characterized in that: The surfactant is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium octyl sulfonate, and potassium octyl sulfonate.

3. The method for preparing an adhesive slide according to claim 1, characterized in that: The auxiliary agents are polyethylene glycol and sodium citrate. The mass fraction of polyethylene glycol in the adhesion solution is 0.05-0.2%, and the mass fraction of sodium citrate is 0.025-0.1%.

4. The method for preparing an adhesive slide according to claim 1, characterized in that: The weight average molecular weight of the polyethyleneimine is 100,000-750,000.

5. The method for preparing an adhesive slide according to claim 1, characterized in that: The silane coupling agent includes one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, 3-diamino-methyl-cyclohexyltriethoxysilane, and γ-aminoethylaminopropyltrimethoxysilane.

6. The method for preparing an adhesive slide according to claim 1, characterized in that: The volume fraction of the silane coupling agent in the silane coupling agent solution is 0.2-1%, and the ethanol aqueous solution with a volume fraction of 93-96% is used as the solvent.

7. The method for preparing an adhesive slide according to claim 1, characterized in that: In step 1, the hydroxylation treatment is to place the glass slide in a 0.8-1 mol / L sodium hydroxide solution and treat it at 60-80° C. for 15-30 minutes.

8. The method for preparing an adhesive slide according to claim 1, characterized in that: In step 2, the activation treatment temperature is 50-60°C and the treatment time is 1-3h.

9. The method for preparing an adhesive slide according to claim 1, characterized in that: The drying is carried out at 60-80°C for 10-60 minutes.

10. An adhered glass slide obtained according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method and using method of hydrophilic adhesive glass slide

    CN104502619A

  • Preparation method of three-dimensional biological chip substrate

    CN104761745A

  • Production method of multifunctional vascular stent coating allowing anticoagulation, rapid endothelialization and proliferation suppression

    CN104841023A

  • Functional modification method for surface and interface of material based on polyphenol compounds

    CN105218847A

  • High-stability low-stripping-rate hydrophilic liquid-based adhesive glass slide and preparation method thereof

    CN111982620A